G. E. Wright at the Harvard Semitic Museum - Gavin, Carney E. S. ca. 1. Hälfte des 20. Jh. - (The Biblical archaeologist, 1987)
Out of all the activities in a life of service, Wright's success as curator of the Semitic Museum is probably his least-acknowledged accomplishment.